Analysis of completeness of reporting utilizing the Reporting Items for practice Guidelines in Healthcare Statement in gastroenterology clinical practice guidelines. Issue 3 (September 2019) - Howard, Benjamin; Chapman, Chris; Meyer, Chase; Walters, Corbin; Vassar, Matt
ABSTRACT: Aim: Assessing reporting quality is important as it allows distinctions to be made between poor methodology and poor reporting practices. The Reporting Items for practice Guidelines in Healthcare (RIGHT) Statement checklist was published in 2017 to improve the thoroughness and reporting quality of clinical practice guidelines (CPGs). CPGs are evidence-based recommendations developed to assist clinician decision-making in the diagnosis and management of patients. The aim of this study is to assess the completeness of reporting in CPGs listed by the American College of Gastroenterology (ACG) and their frequency of reporting items listed in the RIGHT Statement. Methods: Using the 22 criteria (35 items) of the RIGHT Statement checklist, two researchers independently documented the adherence to each item for all eligible guidelines listed by the ACG. This study was conducted from 01/10/18 to 05/12/18. Data were recorded onto a prespecified Google data abstraction form and extracted into MS Excel for statistical analysis. Results: Out of 38 eligible guidelines, nine of the 35 RIGHT (25.7%) checklist items were met with less than 50% adherence. The mean adherence was 26.8 (SD ± 9.5); median adherence was 30 (interquartile range 21.5–33.5). The publication dates ranged from 2007 to 2017 with seven of the guidelines (18.4%) published between 2007 and 2009, 11 (29%) published between 2010 and 2013, and 20 (52.6%) published between 2014 and 2017. Conclusion: The completeness of reporting in CPGs listed by the ACG remains inadequate in several key areas. Poor adherence to items of the RIGHT Statement checklist demonstrates that there is area for improvement in reporting quality.